The Abundance and Diversity of Plankton in the Waters of the Tasilaha Lagoon Helpano Village, South Banawa, Donggala Regency - Moh. Sabran; Syech Zainal; Aan Febriawan (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2022)
Plankton are organisms (animals and plants) that live floating or floating in the water column, their movement is influenced by currents. The role of plankton is very important in aquatic ecosystems, especially phytoplankton which are primary producers. This research is a quantitative descriptive study using purposive sampling method with a field and laboratory survey approach. The purpose of the study was to describe the abundance and diversity of plankton in the waters of the Tasilaha Lagoon. This research was conducted in June – July 2022. The results of the study were 31 types of plankton consisting of 17 types of phytoplankton and 14 types of zooplankton. The abundance of phytoplankton species obtained ranged from 366–5,597 cells/liter and zooplankton 623–5,515 individuals/liter. The value of the phytoplankton diversity index was 2.44–2.55 and the zooplankton ranged from 2.19–2.31.